1993
DOI: 10.1046/j.1525-1438.1993.03020065.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary adenocarcinoma of the fallopian tube. Review of the literature

Abstract: An extensive review of the currently available literature on primary fallopian tube carcinoma is presented. The role of vaginal ultrasonography and the importance of an aggressive evaluation of every tubal deformity is stressed. A staging system which takes into account recent data on the biology of this malignancy is proposed. We emphasize the largely underestimated importance of early lymphatic spread of this disease, necessitating a thorough staging laparotomy with pelvic and para-aortic lymph node sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
7

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 40 publications
1
28
0
7
Order By: Relevance
“…Vaughan et al [46] reported a rate of 21% of preoperative diagnosis, Baekelandt et al [28] reported a rate of only 2%, and Meng et al [17] reported that an intraoperative diagnosis is missed in up to 50% of patients. Some patients have been found to have extensive pelvic tumor, perhaps manifested by a tubo-ovarian mass.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Vaughan et al [46] reported a rate of 21% of preoperative diagnosis, Baekelandt et al [28] reported a rate of only 2%, and Meng et al [17] reported that an intraoperative diagnosis is missed in up to 50% of patients. Some patients have been found to have extensive pelvic tumor, perhaps manifested by a tubo-ovarian mass.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…On routine lymphadenectomy, 42%-59% of patients show lymph node metastases, with almost equal involvement of the para-aortic and pelvic lymph nodes [34]. Compared with EOC, nodal spread is more common in PFTC, and therefore these observations provide the basis for recommending lymph node sampling as a mandatory procedure of surgical staging [28,48]. Surgical understaging, as in the case of EOC, was common in older series.…”
Section: Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Tubal karsinomlu olguların %80'inde serum CA-125 seviyeleri yüksek saptanabilmektedir. 10,11 Hefler ve ark., primer tubal karsinomlu olgularda ortalama CA-125 değerini 183 U/mL olarak tespit etmişlerdir. 12 Yeni çalışmalarla desteklenmemiş olsa da B-hCG değerinin de marker olabileceği belirtilmiş.…”
Section: Discussionunclassified